Ateliers 88. - Pagé, Suzanne (Paris : ARC Musée d'Art Moderne de la Ville de Paris, 1988)
Andrieu, Jean-Marc ; Boeno, David ; Bond, Peter ; Bonnal, Daniel ; Chevalier, Miguel ; Cuzin, Christophe ; Elie, François ; Jaunet, Marie ; Joisten, Bernard ; Kliaving, Serge ; Lallemand, Stephane ; Marcel, Didier ; Marcheschi, Jean-Paul ; Yan Pei-Ming ; Othoniel, Jean-Michel ; Renard, Joël ; Smith, Seton ; Stratmann, VEit ; Villemin, Jean
Ateliers 88, ARC Musée d'Art Moderne de la Ville de Paris, 28 avril - 26 juin 1988
Frans
kunstcatalogus